2022
DOI: 10.1016/j.cgh.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2-specific Humoral and T-cell Immune Response After Second Vaccination in Liver Cirrhosis and Transplant Patients

Abstract: Background and Aims Detailed information on the immune response after second vaccination of cirrhotic patients and liver transplant (LT) recipients against SARS-CoV-2 is largely missing. We aimed at comparing the vaccine-induced humoral and T-cell responses of these vulnerable patient groups. Methods In this prospective cohort study, anti-SARS-CoV-2 spike-protein titers were determined using the DiaSorin LIAISON (anti-S Trimer) and Roche Elecsys (anti-S RBD) immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
217
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(247 citation statements)
references
References 25 publications
22
217
1
7
Order By: Relevance
“…No sex differences in the rate of long-term vaccine antibody response were detected. This agrees with previous reports 11,18,22 but is in contrast to what was reported in LT recipients by Herrera et al 19 , who documented a significantly lower response rate in females. However, this difference may be due to the different vaccine types (mRNA1273) adopted in these patients compared to BNT162b2 adopted in our patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No sex differences in the rate of long-term vaccine antibody response were detected. This agrees with previous reports 11,18,22 but is in contrast to what was reported in LT recipients by Herrera et al 19 , who documented a significantly lower response rate in females. However, this difference may be due to the different vaccine types (mRNA1273) adopted in these patients compared to BNT162b2 adopted in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the peak of responder patients J o u r n a l P r e -p r o o f was reached four months after the second vaccine dose and remained stable up to six months. Recent reports indicated that the rate of antibody response to anti-SARS-CoV-2 vaccination in LT patients ranged from 45.5% to 82% 11,12,16,[18][19][20][21][22] , which is comparable to what we observed. However, all these studies evaluated the early (up to 3 months) immune response to vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the importance of the quantitative level of circulating antibodies, IgG and IgA, to this respiratory infection remains unclear, taking issues such as t-cell-mediated immunity and the definition of neutralizing antibodies into account. Ruether et al, in whose cohort of LT recipients a seroconversion rate of 63% regarding anti-spike-protein-IgG was achieved, detected a spike-specific T-cell response in 36.6% in the same cohort compared to a cohort of patients with liver cirrhosis and healthy controls, who both developed anti-spike-protein-IgG in 100% of the cases and had a spikespecific T-cell response in 65.4 and 100% of the cases, respectively [26]. Westhoff et al detected a seroconversion rate of 60% and anti-spike-specific T-cells in 90% of kidney transplant recipients following a third dose of mRNA-based vaccine following initial humoral nonresponse following the second dose [27].…”
Section: Discussionmentioning
confidence: 94%
“…Double-negative patients even accounted for 28%. For patients with liver cirrhosis in this cohort, the serum conversion rate after the second vaccination can reach 100% [66] . Based on the above research and position statements issued by the EASL and AIFA [ 67 , 68 ], the following suggestions are listed for reference: [1] Patients with noncirrhotic NAFLD and ALD seem to be at high risk of severe COVID-19.…”
Section: Treatment and Vaccination Suggestions For Cld (Including Lt) Patientsmentioning
confidence: 86%